2021
DOI: 10.3389/fnut.2021.801228
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Salt Intake and Gastric Cancer Risk: A Systematic Review and Meta-Analysis

Abstract: The results of prospective cohort studies regarding the role of salt intake and subsequent gastric cancer risk are inconsistent. Thus, we performed a systematic review and meta-analysis to summarize the strength of the association of salt intake with gastric cancer morbidity and mortality. PubMed, EmBase, and Cochrane Library were systematically searched to identify eligible studies published throughout September 2021. The effect estimates with 95% confidence intervals (CIs) for gastric cancer morbidity or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 58 publications
(42 reference statements)
2
31
0
1
Order By: Relevance
“…A high-salt diet is a well-established risk factor for cardiac, vascular, autoimmune and chronic inflammatory diseases [ 47 , 48 , 49 ]. Although a direct correlation between high-salt diet and human breast cancer is not readily available in the scientific literature, there are some apparently contradictory findings on the relationship between salt diet and gastric cancer in human versus pre-clinical models [ 50 , 51 , 52 ]. Human studies by Wilck et al demonstrated that HS diet induces the depletion of Lactobacilus , generally considered good bacteria, in the gut microbiome, leading to the aggravation of autoimmune diseases in a murine model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high-salt diet is a well-established risk factor for cardiac, vascular, autoimmune and chronic inflammatory diseases [ 47 , 48 , 49 ]. Although a direct correlation between high-salt diet and human breast cancer is not readily available in the scientific literature, there are some apparently contradictory findings on the relationship between salt diet and gastric cancer in human versus pre-clinical models [ 50 , 51 , 52 ]. Human studies by Wilck et al demonstrated that HS diet induces the depletion of Lactobacilus , generally considered good bacteria, in the gut microbiome, leading to the aggravation of autoimmune diseases in a murine model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data suggested that the IL‐17F produced by salt‐induced Th17 cells activated the MAPK signalling in breast cancer cells 152 . In humans, high salt intake is a risk factor for lung, testicular, bladder, 182 renal cell, 183 pancreatic, 184 oesophageal 181 and gastric cancer 180 . Particularly, an HSD can promote Helicobacter pylori infection, gastric mucosa damage, hypergastrinemia and cell proliferation, therefore contributing to gastric carcinogenesis 153 .…”
Section: The Effect Of High‐salt Diet On Immune‐regulated Diseasesmentioning
confidence: 99%
“…Meanwhile, soybean protein ingredients are considered as key components of plant protein-based dietary patterns for their high quality and proven health benefits. , A series of epidemiological studies from East Asian countries (China, Japan, and Korea) indicated that high consumption of non-fermented soybean foods was associated with a decreased risk of gastric cancer (GC). GC is the third most common cause of cancer-related deaths in the world and one of the most frequent cancers in East Asian countries, especially in China, where the morbidity and mortality of GC were 480,000 and 500,000 in 2017, respectively . It has been suggested that the major risk factors of GC are high-sodium diets , and Helicobacter pylori (H. pylori) infections .…”
Section: Introductionmentioning
confidence: 99%